2015
DOI: 10.1371/journal.pone.0128457
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Nanoparticles Affect Bacillus subtilis Cell Growth and Biofilm Formation

Abstract: Zinc oxide nanoparticles (ZnO NPs) are an important antimicrobial additive in many industrial applications. However, mass-produced ZnO NPs are ultimately disposed of in the environment, which can threaten soil-dwelling microorganisms that play important roles in biodegradation, nutrient recycling, plant protection, and ecological balance. This study sought to understand how ZnO NPs affect Bacillus subtilis, a plant-beneficial bacterium ubiquitously found in soil. The impact of ZnO NPs on B. subtilis growth, Ft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(55 citation statements)
references
References 51 publications
5
50
0
Order By: Relevance
“…Here, we have demonstrated that the presence of ZnO nanoparticles induces a stress that bacteria fight via large modifications of the metabolism. Similar observations have already been described by Hsueh and collaborators [81], who have demonstrated that ZnO nanoparticles affect the viability of Bacillus subtilis through the inhibition of cell growth, cytosolic protein expression and biofilm formation. Our study is a first step to understand, at a physiological level, the long-term adaptation of a gram-positive bacteria in response to nanoparticles.…”
Section: Discussionsupporting
confidence: 88%
“…Here, we have demonstrated that the presence of ZnO nanoparticles induces a stress that bacteria fight via large modifications of the metabolism. Similar observations have already been described by Hsueh and collaborators [81], who have demonstrated that ZnO nanoparticles affect the viability of Bacillus subtilis through the inhibition of cell growth, cytosolic protein expression and biofilm formation. Our study is a first step to understand, at a physiological level, the long-term adaptation of a gram-positive bacteria in response to nanoparticles.…”
Section: Discussionsupporting
confidence: 88%
“…Our study suggests that both ZnO NP-I and ZnO NP-II showed significant an- et al, [29] and Mastanaiah et al [30] demonstrated the anti-Bacillus subtilis activity of ZnO nanoparticle and Lawsonia inermis respectively suggesting the antibacterial potential of ZnO nanoparticle and Lawsonia inermis.…”
Section: Antibacterial Activity Of Zno Nanoparticles Against B Subtilissupporting
confidence: 53%
“…At lower concentrations also, significant reduction in EPS production was recorded for all pathogens ( Figure 5(a)). Hsueh et al [54] have observed 92% reduced production of EPS by P. aeruginosa upon treatment with 100 ng/ml concentration of copper oxide nanoparticles. LewisOscar et al [55] also reported significant reduction of EPS produced by zinc oxide nanoparticle treated Bacillus subtilis strains.…”
Section: Inhibition Of Eps and Swarmingmentioning
confidence: 99%